Epsilon Haemoglobin Specific Antibodies with Applications in Noninvasive Prenatal Diagnosis. (14th July 2009) - Sørensen, Morten Dræby; Gonzalez Dosal, Regina; Jensen, Kim Bak; Christensen, Britta; Kølvraa, Steen; Jensen, Uffe Birk; Kristensen, Peter
Abstract : Invasive procedures for prenatal diagnosis are associated with increased risk of abortion; thus, development of noninvasive procedures would be beneficial. Based on the observation that embryonic nucleated red blood cell (NRBC) crosses the placenta and enters the circulation of pregnant women, the ability to identify such cell would allow development of such procedures. Identification of NRBCs in blood samples would be possible provided that specific antibodies are available. Here we have isolated recombinant antibodies using phage display. From the panel of antibody fragments specifically recognisingε -Hb, one was chosen for further characterization, DAb1. DAb1 binds toε -Hb both in Western blots and immunocytochemistry. Severalε -Hb positive cells were detected in a blood sample taken as postchorionic villus sampling (CVS). To evaluate the sensitivity of the method, K562 cells (which expressε -Hb) were spiked in a blood sample followed by staining in solution and FACS analysis.